"Standing in the Gap": The Continued Importance of Culturally Competent Therapeutic Interventions for Black Youth. Issue 3 (2nd July 2020) - Jones, Shawn C. T.; Anderson, Riana Elyse; Metzger, Isha W.
ABSTRACT: The mental health status of Black youth is a complex interplay of resilience in the face of risk. Basic and applied research on cultural considerations for Black youth and their families has proliferated over the past few decades – elucidating a number of protective and promotive factors. Nevertheless, there remains a very significant gap between what research and practice say concerning culturally relevant processes and what is routinely done in clinical practice. This article is offered as an attempt to assist applied researchers and clinicians in reducing this gap. To that end, we 1) review the extant literature on culturally relevant factors that positively impact Black youth mental health; 2) articulate how applied research and clinical guidelines have attempted to incorporate these factors into therapeutic practice; and 3) outline a set of recommendations and best practices to optimize the evidence base concerning Black youth, setting the stage for optimal mental health outcomes for these youth and their families.